Correction: A machine learning approach-based array sensor for rapidly predicting the mechanisms of action of antibacterial compounds. Issue 13 (17th March 2022) - Li, Zhijun; Jin, Kun; Chen, Hong; Zhang, Liyuan; Zhang, Guitao; Jiang, Yizhou; Zou, Haixia; Wang, Wentao; Qi, Guangpei; Qu, Xiangmeng
Abstract : Correction for 'A machine learning approach-based array sensor for rapidly predicting the mechanisms of action of antibacterial compounds' by Zhijun Li et al., Nanoscale, 2022, 14, 3087–3096, DOI: ; 10.1039/D1NR07452K .